A Ball for the Refused: Struggle over Literary Freedom within the Dutch Literary Field - van de Warenburg, Marit; van Gaalen, Thomas (FRAME, Journal of Literary Studies, 2026)
Although Bourdieuian scholars have analyzed the literary field’s participation in social struggles, few studies have sought to chart the dynamics of protest and clash that occur within the field. This article aims to provide a first step in doing so through a discourse analysis of the 2002 schism between the Boekenbal (“Book Ball”), a high-profile Dutch literary festival, and its symbolic rival, the Bal der Geweigerden (“Ball of the Refused”), which was announced in response to the Boekenbal’s perceived neglect of literature in favor of commerce. The article shows that the BdG’s inconsistent re-use of dominant narratives and ideas regarding literature and its place in society added to an already growing insecurity about long-held literary values, and might have contributed to the bankruptcy of several of these values throughout the 2000s.